OPPORTUNITIES AND CHALLENGES OF CHATGPT IN CHEMISTRY: NARRATIVES OF PHILIPPINE PRE-SERVICE TEACHERS - Kimberly C. Rivera (Universitas Negeri Surabaya, 2026)
Chemistry, especially redox chemistry, has always presented complex challenges to learners as it expects them to work at several different levels of representation and to connect abstract electron transfer processes to actual phenomena in the real world. These obstacles are compounded in pre-service teachers by the fact that they have to master disciplinary material and at the same time, start forming their own professional pedagogical identities. The study examined how twenty-five first-year teacher education students in a Philippine state university interacted with the ChatGPT as a preparatory intervention to learn the redox reactions and how these perceptions were reflected in their written responses to determine the cognitive and professional consequences of such experience. Using qualitative content analysis, six interrelated themes were generated that describe how students experienced ChatGPT as a learning scaffold, its conceptual affordances, perceived limitations, and its implications for their emerging professional identities. The findings suggest that the use of ChatGPT as a self-directed inquiry and contextualized learning scaffold is valuable, but it requires critical assessment and careful incorporation to avoid misconceptions and overdependence. For teacher education, the research explains that in order to make AI literate, teacher education should also be subject mastery that would enable future teachers to use generative AI in a responsible manner and maintain the human-centered, relational, and ethical aspects of teaching that cannot be technologically-enhanced.